Concrete, Sustainability and Limit States. (June 2019) - Hrabová, K; Teplý, B; Hájek, P
Abstract: Efficient sustainability management of concrete structures requires the use of tools which allow material, technological and construction variants to be quantified. The present contribution, apart from discussing the issue of sustainability of concrete structures, focuses on the quantification of concrete resistance to degradation. An indicator expressing quality, with regard to sustainability, is determined using information on concrete performance characteristics, service life and eco-costs, enabling the quantification and comparison of various cases. Cradle-to-gate system boundary and the full probability method are used. The aim is to propose a suitable methodology which can simplify decision-making about the design and choice of concrete mixes from a wider sustainability perspective, as an extensional and integrating approach to evaluating load-bearing capacity and durability. Two case studies of probabilistic sustainability quantification are shown using sustainability potential indicators for two different definitions of service life (due to carbonation of concrete and freeze/thaw effects), considering also the concrete performance's and impact on the environment.